2013
DOI: 10.1084/jem.20131219
|View full text |Cite
|
Sign up to set email alerts
|

Aging predisposes to acute inflammatory induced pathology after tumor immunotherapy

Abstract: Aging strongly promotes inflammation responses, which may predispose individuals after cancer therapies to lethal system toxicities and pathology that can be partially prevented by TNF blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(146 citation statements)
references
References 61 publications
5
137
1
3
Order By: Relevance
“…These data are different to others who have reported decreased cytokine secretion from elderly macrophages (Corsini et al 1999;Wallace et al 1995). However, a recent conflicting study also showed that macrophages from aged mice produce higher cytokine levels (TNF and IL-6) following in vitro LPS stimulation (Bouchlaka et al 2013). This discrepancy may reflect different technologies, different mouse strains or species, and/or macrophages from different tissue sites; the latter highlighted in a study showing that LPSstimulated splenic macrophages, but not bone marrowderived macrophages, from aging mice demonstrated an aberrant response (Mahbub et al 2012).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…These data are different to others who have reported decreased cytokine secretion from elderly macrophages (Corsini et al 1999;Wallace et al 1995). However, a recent conflicting study also showed that macrophages from aged mice produce higher cytokine levels (TNF and IL-6) following in vitro LPS stimulation (Bouchlaka et al 2013). This discrepancy may reflect different technologies, different mouse strains or species, and/or macrophages from different tissue sites; the latter highlighted in a study showing that LPSstimulated splenic macrophages, but not bone marrowderived macrophages, from aging mice demonstrated an aberrant response (Mahbub et al 2012).…”
Section: Discussioncontrasting
confidence: 60%
“…Our data showed that use of an IL-2/anti-CD40 Ab-based immunotherapy could be effective in elderly cancer-bearing hosts. However, a recent study showed that systemic IL-2/anti-CD40 Ab induces rapid and lethal toxicity in aged mice, mediated by pro-inflammatory macrophages (Bouchlaka et al 2013). Our previous studies observed high lethality in young mice treated systemically with IL-2/anti-CD40 Ab (Jackaman et al 2008).…”
Section: Discussionmentioning
confidence: 91%
“…Only when both antigens are present does sustained T cell priming and activation occur. antibody is more toxic in aged mice and mice with obesity 76 . Treatment with etanercept to block TNF in young, obese mice receiving the same immunotherapy prevented the toxic effects of cytokine storm 77 .…”
Section: Box 1 Adoptive T Cell Therapymentioning
confidence: 99%
“…The majority of laboratory studies using vertebrates are done with young animals which may be appropriate to model the biology of young humans. Conversely, older animals may be more appropriate for studies of human conditions and diseases prevalent in older humans, as suggested in some published work (Bouchlaka et al 2013). However, there are two primary obstacles to such studies: cost and time.…”
Section: Current Activitiesmentioning
confidence: 99%